2016
DOI: 10.1001/jamapediatrics.2015.3065
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Atopic Disease and Anemia in US Children

Abstract: IMPORTANCE Atopic disease is associated with chronic inflammation, food allergen avoidance, and use of systemic immunosuppressant medications. All these factors have been shown to be associated with anemia. OBJECTIVE To investigate whether atopic disease is associated with increased risk of childhood anemia. DESIGN, SETTING, AND PARTICIPANTS A cross-sectional survey and laboratory assessment were conducted using data from the 1997-2013 US National Health Interview Survey (NHIS) that included 207 007 children a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 35 publications
4
47
0
Order By: Relevance
“…Even though an association with atopic diseases (allergic rhinitis, atopic dermatitis, and asthma), designated the atopic match (allergic match), was shown [24][25][26], there could be differences in the magnitude of inflammation among the atopic diseases. Two previous studies reported that the more atopic diseases patients have, the higher their risk of anemia [14,15]. Our results were in agreement.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Even though an association with atopic diseases (allergic rhinitis, atopic dermatitis, and asthma), designated the atopic match (allergic match), was shown [24][25][26], there could be differences in the magnitude of inflammation among the atopic diseases. Two previous studies reported that the more atopic diseases patients have, the higher their risk of anemia [14,15]. Our results were in agreement.…”
Section: Discussionsupporting
confidence: 93%
“…Drury et al investigated the association between atopic diseases and anemia using a survey of pediatric and adolescent patient caregivers [14]. The present study could better support the results, as it used diagnostic codes for each disease.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Indeed, our data showed that ~80% of patients with AD who had increased CLA − T‐cell activation suffered from asthma, food allergies, or environmental allergies . Additionally, increased ‘systemic T‐cell activation may also account for the systemic comorbidities that are now becoming increasingly recognized in patients with severe AD .…”
Section: Circulating Cla+ T Cells Are Functionally Related To Ad Cutamentioning
confidence: 82%
“…One study has implicated sleep disturbance as a contributing factor, 12 and two studies have implicated AD severity. 4,6 Childhood AD is also associated with multiple allergic and nonallergic comorbidities that might further contribute to the increased risk of ADD/ADHD, including obesity, [13][14][15] anaemia, 16 headaches, 17 asthma 18 and allergic rhinitis. 18 We hypothesized that AD is independently associated with increased risk of ADD/ADHD in children, and that disease severity and sleep disturbance act in concert to increase the risk of ADD/ADHD.…”
mentioning
confidence: 99%